Daily gridded weather for pesticide exposure modeling. (August 2016) - Fry, Meridith M.; Rothman, Gabriel; Young, Dirk F.; Thurman, Nelson
Abstract: Daily weather is compiled for pesticide exposure modeling from 1961 to 2014 at 0.25 × 0.25° latitude/longitude resolution for the United States using two National Oceanic and Atmospheric Administration (NOAA) products: National Center for Environmental Prediction Reanalysis and NOAA Climate Prediction Center Unified Rain Gauge Analysis. The compiled weather includes precipitation, temperature, wind speed, solar radiation, and reference evapotranspiration. Reference evapotranspiration is calculated using the Hargreaves-Samani method. Prior to this update, US pesticide exposure models relied upon the Solar and Meteorological Surface Observation Network dataset, which provides the same variables but only from 1961 to 1990 for 237 US weather stations. More extensive (1961–2014), spatially-resolved weather allows for more robust estimates of time-averaged pesticide concentrations for assessing acute and chronic exposure to pesticides. Continued expansion of the weather dataset is planned as the latest data is released. Processed weather for pesticide exposure modeling will be publicly available from the US EPA. Highlights: Daily, gridded weather is compiled from 1961 to 2014 for chemical transport modeling. Reference evapotranspiration is calculated empirically and included in the dataset. The dataset improves the spatial and temporal resolution of US pesticide models. The updated weather allows for more robust estimates of acute and chronic exposure.